The housing tenure of immigrants in Ireland: Some preliminary analysis - David Duffy (The Economic and Social Research Institute (ESRI), 2007)
A feature of the Irish economy in recent years has been the high net flow of people into the country. The analysis compares owner-occupancy by natives and immigrants in 1995 and 2004. The results show that immigrants have higher headship rates than the native population but have a much lower rate of owner-occupancy than natives and that the gap has widened over time. The longer an immigrant has been resident in Ireland the more likely they are to be homeowners. The changing mix of the immigrant population may be a contributing factor in explaining the widening gap.
Keywords: J61; R21; 330; Wohneigentum; Migranten; Schätzung; Irland